Assessment of DNA-binding affinity of cholinesterase reactivators and electrophoretic determination of their effect on topoisomerase I and II activity - Janockova, J; Zilecka, E; Kasparkova, J; Brabec, V; Soukup, O; Kuca, K; Kozurkova, M (Molecular bioSystems, 2016)
In this paper, we describe the biochemical properties and biological activity of a series of cholinesterase reactivators (symmetrical bisquaternary xylene-linked compounds, K106-K114) with ctDNA. The interaction of the studied derivatives with ctDNA was investigated using UV-Vis, fluorescence, CD and LD spectrometry, and electrophoretic and viscometric methods. The binding constants K were estimated to be in the range 1.05 × 10(5)-5.14 × 10(6) M(-1) and the percentage of hypochromism was found to be 10.64-19.28% (from UV-Vis titration). The used methods indicate that the studied samples are groove binders. Electrophoretic methods proved that the studied compounds clearly influence calf thymus Topo I (at 5 μM concentration, except for compounds K107, K111 and K114 which were effective at higher concentrations) and human Topo II (K110 partially inhibited Topo II effects even at 5 μM concentration) activity.
Keywords: DNA Topoisomerases, Type II; denaturace nukleových kyselin; DNA Topoisomerases, Type I; viskozita; Protein Binding; Circular Dichroism; Viscosity; DNA-topoisomerasy I; molekulární struktura; spektrální analýza; Molecular Structure; DNA; cirkulární dichroismus; DNA-topoisomerasy typu II; Nucleic Acid Denaturation; vazba proteinů; reaktivátory cholinesterasy; Cholinesterase Reactivators; Spectrum Analysis